Il libero arbitrio. Un’illusione umana? - Fotia, Francesco; Stancati, Claudia; Perrelli, Raffaele (Università della Calabria, 2023)
An agent who has Free Will is an agent who 1) has full control over her own choices and an agent who 2) can choose at least between two courses of action. The “Free will Problem" arises when we wonder if the laws of the world we live in allow us to be free. If the world works deterministically then, given the past, there is only one possible future. This rules out an agent having real access to choices. If the world works in an indeterministic way, no one can cause an event, then an agent cannot have full control over her own choices.
Dottorato di ricerca internazionale di Studi umanistici: Testi, saperi, pratiche: dall'antichità classica alla contemporaneità, Ciclo XXXV. a.a. 2022-2023
Keywords: Epifenomenismo; Free will; Compatibilismo; Determinismo; Scetticismo